Praktik Murabahah Emas Pada Bank Syariah di Indonesia Berdasarkan Tinjauan Hukum Fiqih Muamalah - Juni Marianti, Dina; Rasyida, Zulfa; Utami, Ema (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2022)
Background. This study exists to examine the concept of investing or saving gold in Islamic banks which is carried out with the murabahah (buying and selling) financing model. Researchers found a problem, namely in the murabahah contract, and the gold payment mechanism which was carried out by means of fixed monthly installments.Aim. This paper aims to present the practice of gold murabahah at Bank Mandiri Syariah as an evaluation of the practice of saving gold with gold murabahah contracts in Islamic banksMethods. This study uses a comparative approach analysis method by analyzing the comparative law used by Islamic banks, namely the DSN MUI fatwa with a review of Fiqh muamalah according to the number of scholars. To explain this, the researcher uses a qualitative descriptive method with a muamalah fiqh approach, through this approach the researcher suggests how to practice according to the Shari'a.Results. The researcher found that there were differences of opinion among scholars regarding the concept of murabahah, and gold installments which the majority of scholars forbade it. Therefore, this study contributes to the analysis of the practice of saving gold in Islamic banks based on the fiqh muamalah review.